Screen design: composing with dynamic symmetry - Ngo, D (2001)
This paper considers a technique for analysing the composition information of displays based on Hambidge's dynamic symmetry. While, by using this technique, our study of dynamic symmetry that underlies 150 real screens shows an unmistakable use of plan schemes of the system in 40% of them, few adhere absolutely to it. It is hard to say if their use was intentional. The use of dynamic symmetry as a screen layout technique has not been mentioned so far because so little is known about it. However, such technique can have a substantial impact on the user's perception of interface aesthetics. (C) 2001 Elsevier Science B.V. All rights reserved.